Postoperative complications after central nervous system tumor resection in pediatric patients admitted to an intensive care unit in Colombia - Lasso-Palomino, Rubén E.; Gómez, Inés Elvira; Soto-Aparicio, María José; Gempeler, Andrés; Pombo-Jiménez, Andrés; Gómez-Toro, Melissa; Rojas-Robledo, Valentina; Jiménez-Arévalo, María Alejandra; Bastidas-Toro, Karla Alejandra; Sierra, Jimena; Martínez-Betancur, Sofía; Ariza-Insignares, Camila; et al. (Frontiers in Oncology, 2024)
IntroductionCentral nervous system (CNS) tumors are the second most prevalent malignant neoplasms in childhood, with surgical resection as the primary therapeutic approach. The immediate postoperative period following CNS tumor resection requires intensive care to mitigate complications associated with high morbidity and mortality. ObjectiveThe primary aim of this study is to comprehensively describe the postoperative complications observed in pediatric patients who underwent primary CNS tumor resection and were subsequently admitted to the pediatric intensive care unit (PICU) at Hospital Universitario Fundación Valle del Lili in Colombia.MethodsWe conducted a cross-sectional observational analysis of pediatric patients who underwent surgery for CNS tumors and were admitted to our PICU from January 2011 to December 2021. Clinical, histopathologic, and postoperative complication data were collected. A descriptive statistical analysis was performed using measures of dispersion and central tendency with a 95% confidence interval.ResultsA total of 114 patients were included, of whom 55.3% were male. The median PICU stay was 4 days (2–7). The most common tumor type was embryonal (25.4%), followed by low-grade glioma (20.1%) and high-grade glioma (14.9%). Mechanical ventilation was required in 24.5% of patients, with a median extubation time of 3 days (2–9). In the immediate postoperative period, 6.14% of patients experienced CNS hemorrhage and 3.5% experienced intracranial hypertension. Common complications included motor deficits, facial paralysis, and sensory deficits. The mortality rate was 3.5%.ConclusionThis study describes the postoperative complications, clinical challenges, and interventions observed in pediatric patients after CNS tumor resection in a resource-limited country. Our findings emphasize the importance of tailored interventions and multidisciplinary collaboration to optimize clinical outcomes. Future data comparison from centers sharing similar characteristics will play a crucial role in identifying best practices and enhancing outcomes globally.